2018
DOI: 10.1038/s41598-018-27237-z
|View full text |Cite
|
Sign up to set email alerts
|

Wafer scale BN on sapphire substrates for improved graphene transport

Abstract: Wafer scale (2”) BN grown by metal organic chemical vapor deposition (MOCVD) on sapphire was examined as a weakly interacting dielectric substrate for graphene, demonstrating improved transport properties over conventional sapphire and SiO2/Si substrates. Chemical vapor deposition grown graphene was transferred to BN/sapphire substrates for evaluation of more than 30 samples using Raman and Hall effects measurements. A more than 2x increase in Hall mobility and 10x reduction in sheet carrier density was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 50 publications
3
27
0
1
Order By: Relevance
“…The Raman shift at 1369 cm −1 , which is attributed to the first‐order E 2g symmetry vibrational mode in h ‐BN owing to the in‐plane stretching of B and N atoms, is observed. The sample exposed to 1000 cycles showed a FWHM of 20 cm −1 , comparable with the reported values for BN films fabricated by MBE or by CVD . Considering other III‐nitrides, the FWHM of the Raman spectrum depends on the dislocation density along with stacking faults, misalignment, tilt, and mosaic spread.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The Raman shift at 1369 cm −1 , which is attributed to the first‐order E 2g symmetry vibrational mode in h ‐BN owing to the in‐plane stretching of B and N atoms, is observed. The sample exposed to 1000 cycles showed a FWHM of 20 cm −1 , comparable with the reported values for BN films fabricated by MBE or by CVD . Considering other III‐nitrides, the FWHM of the Raman spectrum depends on the dislocation density along with stacking faults, misalignment, tilt, and mosaic spread.…”
Section: Resultssupporting
confidence: 83%
“…In this respect, wafer‐scale thin‐film growth methods, such as CVD or molecular beam epitaxy (MBE), are preferable to realize device applications. Many research groups have reported thermal CVD of BN thin films with a wide variety of boron precursors, such as borazine (B 3 N 3 H 6 ), boron‐halides (BF 3 , BCl 3 , and BBr 3 ), and triethyl boron ((C 2 H 5 ) 3 B, TEB), on sapphire, SiC, Ni, and Cu substrates. For borazine, it is difficult to control the N/B ratio, which leads to turbostratic boron nitride ( t ‐BN), a disordered phase of h ‐BN.…”
Section: Introductionmentioning
confidence: 99%
“…The values are comparable to the BN films fabricated by MBE [31] or by CVD. [14][15][16][19][20][21]24] By decreasing the T g down from 1360 to 1140 C, the FWHM of the Raman shift increased from 20 to 28 cm À1 . The lower T g induces a higher density of crystalline defects, such as dislocation along with stacking faults, misalignment, tilt, and mosaic spread, which would affect Raman spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…[31] The growth conditions include a wide varieties of boron precursors of borazine (B 3 N 3 H 6 ), [8] boron halides (BF 3 , BCl 3 , BBr 3 ), [9,25] triethylboron ((C 2 H 5 ) 3 B, TEB), [5][6][7][10][11][12][13][14][15][16][17][18][19][20][21] trimethylboron ((CH 3 ) 3 B, TMB), [22] and diborane (B 2 H 6 ). [23,24] Also, various substrates for BN growth were investigated, such as sapphire, [5][6][7][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] SiC, [22] Ni, [21,24] and Cu. [8] High-purity BN films would be expected using B 2 H 6 gas because it does not contain Cl, Br, or C atoms in the raw material.…”
Section: Introductionmentioning
confidence: 99%
“…Hall effect measurements from as-transferred graphene on BN/sapphire substrates found all samples were p-type prior to device processing with an average hole concentration of 4 × 10 12 cm -2 and mobility of 1,860 cm 2 / Vs. This shift in carrier type after device fabrication is due to significant n-type doping caused by deposition of the Al 2 O 3 gate dielectric 9,35 . Devices with only the BN buffer layer and both the BN and Al layer show a switch in the direction of I ds dependence on V G .…”
Section: Resultsmentioning
confidence: 99%